Learners’ Perceptions Towards The KBSM English Literature Component - Mohd. Nawi, Abdullah; Lim, Andrew Ming Yew (2010)
This study explores learners’ perceptions towards the KBSM English Literature component for upper secondary. The focus of this study is on learners’ perspectives and attitudes towards the component, their perspectives towards their teachers’ teaching of the component, as well as teachers’ perspectives towards the component. Two groups of learners were involved, namely current learners and ex-learners. 50 students from a secondary school in Skudai and 50 undergraduates of the Faculty of Education, Universiti Teknologi Malaysia, as well as 4 upper-secondary English teachers contributed to the findings of this study. Questionnaire was used as the instrument for the collection of data. Descriptive statistics was used in the analysis of data, specifically in the form of mean. Data obtained from current learners were compared to the data obtained from ex-learners. On the whole, the results of this study showed marginal differences between the two groups of learners surveyed.